Η επίδραση του υδρογόνου στην καύση υψηλής συγκέντρωσης μείγματος βιοντίζελ/πετρελαίου σε μηχανή εσωτερικής καύσης - Θεοδώρου, Λούκας (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
The energy problem began emerging as early as 1950 at which time fossil fuel deposits were estimated to last for 20 years. However, the appropriate attention was not given while energy needs were rapidly increasing, and in 1973 the event of an energy crisis unfortunately increased the energy problem which today is more intense due to the rapid decline of economically accessible reserves of fossil fuels. The energy problem can be solved if methodical exploitation of hydrogen (H2), which is available plenty of nature, is done right. The advantages and benefits that will be created by facing the problem, are too many, such as reducing the use of hydrocarbons, extending the protection of the environment, energy abundance of H2, and energy decentralization. The purpose of the Graduate Thesis is to indicate the use of hydrogen (H2) as a fuel in combination with a mixture of biodiesel / petroleum diesel engines (I.C.E). The aim of the G.T is to indicate that an optimum combination of conventional diesel fuel with biodiesel renewable fuel and hydrogen, achieves both the reduction of diesel consumption and reduction of air emissions. This Graduation Thesis will indicate the urgent issue of the environment that prevails nowadays due to the combustion of fossil fuels and the gaseous emissions that arise.
Keywords: Mixture diesel/biodiesel/hydrogen; NOx; NO; CO; Electrolysis; Internal Combustion Engine(I.C.E); Μείγμα ντίζελ/βιοντίζελ/υδρογόνο; Μηχανές Εσωτερικής Καύσης (ΜΕΚ); Ηλεκτρόλυση